Sistem Peringatan Dini Banjir Sungai Bengawan Solo Menggunakan Teknologi Internet Of Things (IoT) - Nanang Maulana Yoeseph; Arif Purwo Nugroho; Andri Adi Nugroho; Agung Eko Saputro (IJAI (Indonesian Journal of Applied Informatics), 2018)
Flood disaster is a natural disaster that causes many losses, both soul and meteriil. Bengawan Solo River is one of the rivers that every year experiencing flood disaster. To improve preparedness for flooding in solo bengawan river, a flood early warning system was created using the Internet of Things (IoT) technology. This system consists of a water level detector, using ultrasonic sensors and arduino uno, and iot servers. Information about the water level of the bengawan solo river can be accessed by users through the website and android. Users will get river water level infromation in real time. Warning level can be set independet for each user. Flood warnings are sent using sms and notification messages for android versions.